2002
DOI: 10.1021/ma0200118
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Structure Formation of Block Copolymers Containing a Rubbery Amorphous Component

Abstract: Changes of higher-order structure of poly(ethylene glycol)−poly(butadiene) (PEG−PBd) di- and triblock copolymers in isothermal crystallization from microphase-separated melts were studied using time-resolved synchrotron small-angle X-ray scattering (SR−SAXS) techniques. Lamellar microphase structure of PEG−PBd with weight fractions f PEG = 0.57 and 0.51 was destroyed on crystallization and changed to a lamellar structure distinct from that in the melt. A diblock copolymer with f PEG = 0.34 crystallized, keepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 18 publications
5
54
1
Order By: Relevance
“…In our previous papers, it was found that the Avrami indices were reduced for block copolymers having a glassy amorphous component, because crystallization occurs within confined rigid microdomains 19,20) . On the other hand, for PEG-PBD, in which the amorphous component is rubbery in crystallization, we reported that the Avrami index is not reduced even when crystalline PEG is in cylindrical microdomains 26) . In the system studied here, the reduction of n was not found even in the blends with the small amount of the crystalline component (HEI/LPIp-17 and HEI/HPIp-17).…”
Section: Crystallization Behavior Of Hei/pe and Hei/pip Blendsmentioning
confidence: 69%
See 3 more Smart Citations
“…In our previous papers, it was found that the Avrami indices were reduced for block copolymers having a glassy amorphous component, because crystallization occurs within confined rigid microdomains 19,20) . On the other hand, for PEG-PBD, in which the amorphous component is rubbery in crystallization, we reported that the Avrami index is not reduced even when crystalline PEG is in cylindrical microdomains 26) . In the system studied here, the reduction of n was not found even in the blends with the small amount of the crystalline component (HEI/LPIp-17 and HEI/HPIp-17).…”
Section: Crystallization Behavior Of Hei/pe and Hei/pip Blendsmentioning
confidence: 69%
“…On the other hand, when crystallized at the intermediate crystallization temperatures (60ՅT c Ͻ94°C), the peak from the microphase separation structure in the melt disappears completely, indicating that the microphase separation structure was disrupted in crystallization of the E block. For crystalline-rubbery amorphous block copolymers, we reported the crystallization of PEG-PBD diblock copolymers, in which PBd is rubbery in crystallization of PEG 26) . In the crystallization of PEG-PBD, reorganization of the phase structure depended on the crystallization temperature as well as the microphase separation structure, i.e., the melt structure tends to be preserved at lower T c , while it is reorganized to the alternating structure of crystalline and amorphous layers at higher T c .…”
Section: Structure Formation In Crystallization Of the Neat Copolymermentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12] In immiscible polymer blends and block copolymers, competition or combination between crystallization and phase separation affects both crystallization and the resulting structure. [5][6][7] Especially in the crystallization of block copolymers from microphase-separated melts, the restriction of crystallization by microdomains is also important. [7][8][9][10] By contrast, for miscible polymer blends, the kinetics of crystallization is affected by diluent effects and by the composition-dependent glass transition temperature (see Mandelkern, 2 Chapter 11).…”
Section: Introductionmentioning
confidence: 99%